Making rare events typical in Markovian open quantum systems - Carollo, Federico; Garrahan, Juan P.; Lesanovsky, Igor; Pérez-Espigares, Carlos (American Physical Society, 2018)
Large dynamical fluctuations—atypical realizations of the dynamics sustained over long periods of time—can play a fundamental role in determining the properties of collective behavior of both classical and quantum nonequilibrium systems. Rare dynamical fluctuations, however, occur with a probability that often decays exponentially in their time extent, thus making them difficult to be directly observed and exploited in experiments. Here, using methods from dynamical large deviations, we explain how rare dynamics of a given (Markovian) open quantum system can always be obtained from the typical realizations of an alternative (also Markovian) system. The correspondence between these two sets of realizations can be used to engineer and control open quantum systems with a desired statistics “on demand.” We illustrate these ideas by studying the photon emission behavior of a three-qubit system which displays a sharp dynamical crossover between active and inactive dynamical phases.